Integration of Distributed Energy Resources to Unbalanced Grids Under Voltage Sags With Grid Code Compliance - Rolan, Alejandro; Bogarra, Santiago; Bakkar, Mostafa (IEEE transactions on smart grid, 2022)
The aim of this paper is to analyze the situations in which distributed power generation systems (DPGSs) based on renewable energy sources (RESs) can be controlled when operating under voltage sags. Analytical models for both solar photovoltaic (PV) system and doubly-fed induction generator (DFIG)-based wind turbine (WT) written in the complex form of the Park variables are given. Three kinds of control for the grid-side converter (GSC) of a PV system are compared: constant forward voltage control (CFVC), balanced positive -sequence control (BPSC) and the proposed BPSC with grid code requirements (BPSC-GCR). Regarding the rotor-side converter (RSC) of a DFIG-based WT, its controllability is studied considering three different-sized DFIG-based WT units: 6 MW (offshore), 2 MW (onshore) and 7.5 kW (setup). The converter limits are also considered. Simulations carried out in MATLAB reveal that a RES-based DPGS can achieve fault ride-through (FRT) when subject to a certain fault (i.e., with a specific duration and depth), but it may be uncontrollable for different-sized units operating under different faults without considering the grid code requirements. Finally, experimental results prove the robustness of the BPSC-GCR method to let GSCs of PV systems achieve FRT under sags.